Hak Waris dan Keadilan: Menggagas Reformasi Hukum Keluarga dengan Prinsip Maqasid Syariah - Wahyu, Wahyu; Sya'bani, Moh.Adib; Permana, Syahrul Permana (Inovbook, 2024)
This research highlights the urgency of reforming family law, especially in the context of inheritance rights and justice. There are contemporary challenges and new dynamics in family life that require serious attention. Identifying obstacles and injustices in the current inheritance law system is an important basis for formulating solutions that are in accordance with universal values. The aim of writing this article is to provide a holistic view of the issue of inheritance rights and justice in family law. This article aims to detail the principles of Maqasid Sharia and Human Rights (HAM) as a basis for creating an inclusive and fair legal framework. In addition, this article also intends to provide concrete guidance to policy makers, legal practitioners and researchers in considering family law reform. This research uses a qualitative approach and literature study to investigate inheritance rights issues in family law, especially in the Indonesian context. Through analysis of the thoughts of Islamic scholars and scholars, this research tries to summarize differences in perceptions among Muslim communities and analyze the impact of economic inequality on the distribution of inheritance. This research produces. (1). In-depth understanding of differences in perceptions and cultural obstacles in the implementation of inheritance provisions according to sharia in Indonesia, (2). It was found that economic inequality plays an important role in inheritance distribution. Therefore, this article discusses (3) concrete recommendations to improve justice in family law, including the integration of Maqasid Syariah principles in the inheritance law framework. It is hoped that this can make a positive contribution to reforming family law that is more inclusive and responsive to social change.